Tunable Quasi‐Plasticity of Microscale Shape Memory Alloys. Issue 2 (29th October 2018) - Song, Jihwan; Kim, Dongchoul
Abstract: As shape memory alloys (SMAs)‐based devices become smaller in size, the elaborate design of these devices based on an understanding of their shape memory and quasi‐plastic behavior at the small scale is becoming more critical. However, the previous studies overlooked the fact that it is feasible to alter the quasi‐plasticity of SMAs at the small scale and to tune them according to various factors. Here, the feasibility of altering the quasi‐plasticity of microscale SMAs with the direction of applied stress and of tuning them according to the volume ratio of crystalline structures is reported. To achieve this, the dynamic model for SMA is developed and their quasi‐plastic behavior, including phase and crystalline structure transformations, is simulated. The simulation reveals that it is feasible to select the crystalline structure of SMA according to the direction of the applied stress and, more critically, to tune the quasi‐plastic deformation by varying the volume ratio of crystalline structures by up to approximately 600% (i.e., 0.8–5.3%). This study highlights the practical tunability in the design of small‐scale SMA‐based systems. Abstract : Tunable quasi‐plasticity of small‐scale shape memory alloys (SMAs) by various factors is overlooked even though their behavior is becoming critical due to their small scale applications. The quasi‐plasticity of small‐scale SMAs can be altered with the stress direction and crystalline structure volume ratio. This highlights the practical tunability in the design of small scale SMA‐based devices.